Primary Central Nervous System Anaplastic Large Cell Lymphoma, ALK Positive: A Case Series With Literature Review. Issue 2 (23rd April 2022) - Ahrendsen, Jared T; Ta, Robert; Li, Jingwei; Weinberg, Olga K; Ferry, Judith A; Hasserjian, Robert P; Meredith, David M; Varma, Hemant; Sadigh, Sam; Michaels, Phillip D
Abstract: Objectives: Primary central nervous system anaplastic large cell lymphoma, anaplastic lymphoma kinase positive (primary CNS ALCL, ALK+) is a rare CNS lymphoma whose description is limited to case reports. These tumors have a variable clinical course, and prognosis is primarily determined by age. We present the largest case series to date of primary CNS ALCL, ALK+, with observational data. Methods: A retrospective search of multiple academic centers was performed to identify cases of primary CNS ALCL, ALK+. We also performed a review of published cases of primary CNS ALCL, ALK+. Clinical history, radiography, pathology, and genetic testing data were obtained to determine the prognostic implications in the context of clinical course. Results: We identified three cases of primary CNS ALCL, ALK+ from our databases. A literature review identified 30 published reports of 31 individual cases. Clinical features for the combined 34 cases included a median age of 18.5 years, with a male to female ratio of 4.7:1, and the most common symptom was headache. Genetic studies demonstrated an ALK rearrangement by fluorescence in situ hybridization, and a gene fusion assay confirmed an NPM1-ALK gene fusion in one case. Conclusions: We present the largest case series to date of a rare primary CNS lymphoma with additional diagnostic and clinical information.